Epratuzumab modulates B-cell signaling without affecting B-cell numbers or B-cell functions in a mouse model with humanized CD22 - Özgör, Lamia; Brandl, Carolin; Shock, Anthony; Nitschke, Lars (European Journal of Immunology, 2016)
Treatment of systemic lupus erythematosus patients with epratuzumab (Emab), a humanized monoclonal antibody targeting CD22, leads to moderately reduced B-cell numbers but does not completely deplete B cells. Emab appears to induce immunomodulation of B cells, but the exact mode of action has not been defined. In the present study, we aimed to understand the effects of Emab on B cells using a humanized mouse model (Huki CD22), in which the B cells express human instead of murine CD22. Emab administration to Huki CD22 mice results in rapid and long-lasting CD22 internalization. There was no influence on B-cell turnover, but B-cell apoptosis ex vivo was increased. Emab administration to Huki CD22 mice had no effect on B-cell numbers in several lymphatic organs, nor in blood. In vitro exposure of B cells from Huki CD22 mice to Emab resulted in decreased B-cell receptor (BCR) induced Ca2+ mobilization, whereas B-cell proliferation after Toll-like receptor (TLR) stimulation was not affected. In addition, IL-10 production was slightly increased after TLR and anti-CD40 stimulation, whereas IL-6 production was unchanged. In conclusion, Emab appears to inhibit BCR signaling in a CD22-dependent fashion without strong influence on B-cell development and B-cell populations.
Keywords: Antibody therapy; B-cell differentiation; B-cell signaling; Systemic lupus erythematosus

IN VIVO EFFECTS OF EPRATUZUMAB, A MONOCLONAL ANTIBODY TARGETING HUMAN CD22, ON B CELL FUNCTION IN HUMAN CD22 KNOCK-IN (HUKI) MICE - Brandl, Carolin; Özgör, Lamia; Wöhner, Miriam; Shock, A.; Nitschke, Lars (ANNALS OF THE RHEUMATIC DISEASES, 2014)
Created from Fastlane, WoS look-up

The Ligand-Binding Domain of Siglec-G Is Crucial for Its Selective Inhibitory Function on B1 Cells - Hutzler, Stefan; Özgör, Lamia; Naito-Matsui, Yuko; Klaesener, Kathrin; Winkler, Thomas; Reth, Michael; Nitschke, Lars (Journal of Immunology, 2014)
Siglec-G is an inhibitory receptor on B1 cells. Siglec-G-deficient mice show a large B1 cell expansion, owing to higher BCR-induced Ca2+ signaling and enhanced cellular survival. It was unknown why Siglec-G shows a B1 cell-restricted inhibitory function. With a new mAb we could show a comparable Siglec-G expression on B1 cells and conventional B2 cells. However, Siglec-G has a different ligand sialic acid-binding pattern on peritoneal B1 cells than on splenic B cells, and its sialic acid ligands are expressed differentially on these two B cell populations, suggesting that cis-ligand binding plays a crucial role on B1 cells. This observation was further studied by generation of Siglec-G knockin mice with a mutated ligand-binding domain. These mice show increased B1 cell numbers, increased B1 cell Ca2+ signaling, better B1 cell survival, and changes in the B1 cell Ig repertoire. These phenotypes are very similar to Siglec-G-deficient mice. The mutation of the ligand-binding domain of Siglec-G strongly reduces the Siglec-G-IgM association on the B cell surface. Thus, Siglec-G sialic acid-dependent binding to the BCR is crucial for the B1 cell-restricted inhibitory function of Siglec-G and is regulated in an opposite way to that of the related protein CD22 (Siglec-2) on B cells.